Maximising creativity and art with game engine technology - Hodgkinson, Gray (2021)
How does a teacher motivate non-technical students to gain enough proficiency with technology to reach a level where they can be freely creative? This question is at the core for any teacher who teaches complex creative software. At times, technology and creativity appear mutually exclusive, and yet, when someone is able to combine these two abilities, they are able to produce engaging art and design that appears effortless. Art and Design schools aspire to nurture technology and creativity together, and successful outcomes rely heavily on the course designer’s awareness of how this learning is achieved. Assumptions about the learning speed of students are easily over-estimated, especially by course designers who are very experienced and for whom the topic is now second nature. This paper will describe how creative media students were tasked with expressing creativity using the highly technical area of 3D gaming, and how the technology was presented to them in a way that was playful, incremental, motivational, and very powerful in its expressive potential.